1997
DOI: 10.1111/j.1365-2672.1997.tb03303.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the kinetics of water potential variation on bacteria viability

Abstract: I. P O I R I E R , P . -A . MARECHAL A N D P. GERVAIS. 1997. The effect of the kinetics of water potential variation (' 3' ) on the viability of bacteria subjected to hyperosmotic stresses in waterglycerol solution was studied. T h e three bacteria used were Lactobacillus plantarum L-73, Leuconostoc mesentemides LM057 and Escherichia cob TG 1. These strains were submitted to a final water potential of -107.2 MPa, -170.9 M P a and/or -244.7 MPa. I n any case the kinetics of water potential variation was found t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0
2

Year Published

1998
1998
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(18 citation statements)
references
References 20 publications
2
14
0
2
Order By: Relevance
“…For example, the inactivation of MscS channels in patch clamp measurements can be observed only when the pressure is applied gradually (7) over tens of seconds. Finally, there are studies that demonstrate that cell survival depends on the time scale over which the external water potential is changed (10)(11)(12). However, to our knowledge, no work has analyzed how the presence or absence of various MS channels impacts cell survival under time-dependent conditions.…”
mentioning
confidence: 99%
“…For example, the inactivation of MscS channels in patch clamp measurements can be observed only when the pressure is applied gradually (7) over tens of seconds. Finally, there are studies that demonstrate that cell survival depends on the time scale over which the external water potential is changed (10)(11)(12). However, to our knowledge, no work has analyzed how the presence or absence of various MS channels impacts cell survival under time-dependent conditions.…”
mentioning
confidence: 99%
“…For example, survival of Salmonella may be greater when dehydration is gradual. 39 Poirier et al 40 showed that decreasing the rate of change in water potential increased the viability of several bacterial cells likely due to associated reductions in water flow rates across cell membranes. 40 Down-or upregulation of biological processes, such as metabolic rates, DNA repair capabilities, or systems to scavenge reactive oxygen species, during slow dehydration can influence bacterial survival.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…39 Poirier et al 40 showed that decreasing the rate of change in water potential increased the viability of several bacterial cells likely due to associated reductions in water flow rates across cell membranes. 40 Down-or upregulation of biological processes, such as metabolic rates, DNA repair capabilities, or systems to scavenge reactive oxygen species, during slow dehydration can influence bacterial survival. 37,41 However, high relative humidity can also lead to more efficient inactivation of dehydration tolerant bacteria, as shown for Deinococcus radiodurans cells.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…La mesure de la viabilité cellulaire est réa-lisée par la méthode UFC, comme décrit par Poirier et al [8]. …”
Section: Mesure De La Viabilité Cellulaireunclassified
“…L'existence de ces cinétiques optimales peut être expliquée par l'opposition de deux actions sur la viabilité cellulaire. Premièrement, une action positive qui est la diminution lente du potentiel hydrique et deuxièmement, une action négative qui est le temps de résidence des cellules dans une zone critique de potentiel hydrique [8].…”
Section: éTude De Conservation Des éChantillons Déshydratésunclassified